Failure and progression to total hip arthroplasty among the treatments for femoral head osteonecrosis: A Bayesian network meta-analysis - Migliorini, Filippo; Maffulli, Nicola; Baroncini, Alice; Eschweiler, Jorg; Tingart, Markus; Betsch, Marcel (British Medical Bulletin, 2021)
Introduction: Osteonecrosis of the femoral head (ONFH) often leads to secondary osteoarthritis and total hip arthroplasty. Source of data: Recent published literatures. Areas of agreement: There has been increasing focus on the early intervention in ONFH patients to preserve the native hip articulation, reduce pain and improve function. Areas of controversy: Efficacy of surgical strategies for ONFH is debated. Several clinical studies showed controversial results, and the best treatment has not yet been clarified. Growing points: To provide an overview over current treatment options for ONFH compares their failure rates and conversion to total hip arthroplasty (THA) rates. Areas timely for developing research: Core decompression (CD) augmented with autologous bone grafting plus the implantation of bone marrow concentrate can decrease the rate of failure and progression to THA rates compared to CD alone.
CRIS-Team Scopus Importer:2022-07-20
Keywords: arthroplasty; failure; femoral head osteonecrosis; hip